Monarch of the Flute. The Life of Georges Barrère - Toff, Nancy (2005)
Georges Barrère (1876-1944) holds a preeminent place in the history of American flute playing. Best known for two of the landmark works that were written for him--the Poem of Charles Tomlinson Griffes and Density 21.5 by Edgard Varèse--he was the most prominent early exemplar of the Paris Conservatoire tradition in the United States and set a new standard for American woodwind performance.Barrère's story is a musical tale of two cities, and this book uses his life as a window onto musical life in Belle Epoque Paris and twentieth-century New York. Recurrent themes are the interactions of composers and performers; the promotion of new music; the management, personnel, and repertoire of symphony orchestras; the economic and social status of the orchestral and solo musician, including the increasing power of musicians' unions; the role of patronage, particularly women patrons; and the growth of chamber music as a professional performance medium.A student of Paul Taffanel at the Paris Conservatoire, by age eighteen Barrère played in the premiere of Debussy's Prelude to the Afternoon of a Faun. He went on to become solo flutist of the Concerts Colonne and to found the Sociètè Moderne d'Instruments á Vent, a pioneering woodwind ensemble that premiered sixty-one works by forty composers in its first ten years. Invited by Walter Damrosch to become principal flute of the New York Symphony in 1905, he founded the woodwind department at the Institute of Musical Art (later Juilliard). His many ensembles toured the United States, building new audiences for chamber music and promoting French repertoire as well as new American music. Toff narrates Barrère's relationships with the finest musicians and artists of his day, among them Isadora Duncan, Yvette Guilbert, André Caplet, Paul Hindemith, Albert Roussel, Wallingford Riegger, and Henry Brant. The appendices of the book, which list Barrère's 170 premieres and the 50 works dedicated to him, are a resource for a new generation of performers.Based on extensive archival research and oral histories in both France and the United States, this is the first biography of Barrère.
Nancy Toff is vice president and executive editor in the academic/trade division of Oxford University Press, New York, where she acquires and edits all varieties of history books ranging from monographs to reference books to trade books. She is responsible for several book series, including the Very Short Introductions (on all subjects), Oxford History Handbooks, the New Oxford World History, the Oxford Oral History Series, and the Oxford Series on History and Archives. She was previously editorial director of young adult reference and trade reference at Oxford, and before that was vice president and editor at chief at Chelsea House Publishers. She has also worked at Grove Dictionaries of Music, Time-Life Books, and Silver Burdett Press.As a scholar, Nancy Toff is considered one of the leading authorities on the history of the flute. She is the author of four books on the subject, most recently Monarch of the Flute: The Life of Georges Barrère (Oxford University Press, 2005); and the third edition of The Flute Book (also from Oxford, 2012), which is a standard text for flute students and performers. She received the Music Library Association's 1997 Dena Epstein Award for Archival and Library Research in American Music, a Sinfonia Foundation research grant, and an American Musicological Society subvention. In 2012 she received the Distinguished Service Award of the National Flute Association.A frequent and popular speaker at history, library, and music conferences and at universities nationwide, Ms. Toff has served as a consultant to the Library of Congress and Metropolitan Museum of Art. In 2021 she completed her third three-year term as president of the New York Flute Club; she has served on its board of directors since 1986 and is also its archivist. She is a graduate of Harvard University.
Keywords: Barrère, Georges, -- 1876-1944; 19th Century (1801-1900); 20th Century (1901-2000); Biography; Flute; Instrumentalist; Paris (France); New York City (USA)